Usulan Perbaikan Kualitas Kadar SO3 pada Semen OPC Menggunakan Metode Six Sigma di PT - ITP Tbk. - Karina Erianto; M. Muchtar Darmawan (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
PT. ITP Tbk. is a cement company where one of its products is OPC (Ordinary Portlan Cement). One of the problems in OPC Cement is that there are still samples for SO3 levels that do not meet specifications. Determination of SO3 levels is carried out in the process at the Finish Mill Machine. This research was conducted in order to provide suggestions for quality improvement of SO3 levels in the OPC cement. The analytical method used is the Six Sigma method. The measure stage gives the Processability Index of Finish Mill Machines of 0.42 with an out of spec percentage of 14.69%. The analysis stage concludes that the most likely cause of SO3 levels out of spec is the change in engine parameter settings because the engine has been operated for 24 hours continuously. The improve stage proposes to re-schedule the use of machines accompanied by rest time